Vaginal vault leiomyoma after hysterectomy. Case report - Reyna-Villasmil, Eduardo (2021)
Leiomyomas are benign, mesenchymal tumors that usually arise from uterine smooth muscle cells, but can also occur in atypical sites such as the vagina, lungs and vascular structures. Post-hysterectomy vaginal vault leiomyomas are very rare and their etiology has not been determined. Transvaginal ultrasound, computed tomography and magnetic resonance imaging are useful tools for the diagnosis and follow-up of these patients. The definitive treatment is total removal of the tumor to avoid dissemination or inadvertent spillage of occult malignant neoplastic cells. Administration of gonadotropin-releasing hormone analogs or intravascular embolization may be alternative methods to reduce intraoperative blood loss. A case of vaginal vault leiomyoma following hysterectomy is presented.